Influence of sowing time and phosphorus on, phenology, thermal requirement and yield of fenugreek (Trigonella foenum-graecum L.) genotypes - Ram Niwas, R S Sheoran, H C Sharma, P K Panuu, (Journal of Spices and Aromatic Crops, 2000)
Experiments were conducted at Hisar (Haryana, India) to study the effect of sowing time and phosphorus on phenology, thermal requirement and yield of two genotypes of fenugreek (Trigonella foenum-graecum). Genotype HM-65 performed better than T-8 with respect to yield and was more efficient in utilizing heat units. Delayed sowing resulted in significant reduction in time taken for initiation of flowering and maturity in both the genotypes. Thermal requirement decreased with delay in sowing in both the genotypes. Increasing levels of phosphorus up to 60 kg/ha significantly enhanced the yield but heat unit consumption slightly declined in both file genotypes.